Real‐world effectiveness for 12 weeks of ledipasvir–sofosbuvir for genotype 1 hepatitis C: the Trio Health study. Issue 1 (11th October 2016) - Tapper, E. B.; Bacon, B. R.; Curry, M. P.; Dieterich, D. T.; Flamm, S. L.; Guest, L. E.; Kowdley, K. V.; Lee, Y.; Tsai, N. C.; Younossi, Z. M.; Afdhal, N. H.
Abstract: Early data regarding the "real‐world" experience with novel therapies for hepatitis C (HCV) are encouraging. Data are still limited, however, regarding real‐world rates of sustained virologic response (SVR) for ledipasvir–sofosbuvir (LDV‐SOF), particularly for patients with prior treatment failure. We performed a retrospective cohort study of 1597 patients with chronic genotype 1 HCV who were treated using 12 weeks of the following regimens LDV‐SOF±ribavirin (RBV) (n=1521 without RBV, n=76 with RBV). The primary outcome was SVR‐determined at 12 weeks in an intention‐to‐treat design. Prescription according to Food and Drug Administration (FDA) approved labelling (adding RBV for patients with cirrhosis and treatment failure) was assessed in multivariate models. The study population was aged 60 years on average (range 19‐89), 60% male, 50% Caucasian, 43% cared for at an academic centre and 30% cirrhotic. Overall, LDV‐SOF resulted in a 94% SVR rate. Only 44 (2.9%) patients relapsed. LDV‐SOF+RBV yielded SVR in 97% with 0 viral relapses. While cirrhosis and thrombocytopenia were associated with lower odds of SVR, in a multivariable regression model, only treatment at an academic centre and prescriptions contrary to FDA labelling were significantly associated with lower SVR—odds ratios, 0.56 95% CI (0.35‐0.87) and 0.29 95% CI(0.12‐0.68), respectively. The real‐world experience with LDV‐SOF mirrors the SVR rates observed in clinical trials. Efforts to promote prescription within FDA recommendations are warranted.